Utilization of Geant4 Monte Carlo Code for Simulations of Gamma Ray Attenuation Coefficients in Selected Materials - Saleh M. Ben Saleh,; Hajer M. Albangahzi,; Shrifa M. Alarabi, (African Journal of Advanced Pure and Applied Sciences, 2025)
When gamma rays fall on a medium, part of it can penetrate it, while the other part is attenuated in the medium through three main interaction processes: the photoelectric effect, the Compton scattering and pair production. The attenuation of gamma radiation is dependent upon the energy of the incident gamma ray beam, the atomic number and the density of the absorbing medium. Monte Carlo simulation has become a powerful method for modelling and computation of the gamma ray attenuation coefficients in any type of material (pure element, compound and mixture). In this research, gamma ray attenuation coefficients for high atomic number materials such as lead and tungsten and low atomic number materials such as iron and aluminium were computed using Monte Carlo simulations. We utilized the GEANT4 Monte Carlo code to specifically determine the linear attenuation coefficients, mass attenuation coefficients and mean free paths in the materials under study at various photon energies including those emitted from 137Cs, 60Co and 152Eu sources. A simulation model was built consisting of a narrow photon beam, thin target and a detection region. The thickness of the target was optimized to avoid that all incident gamma rays were absorbed in the target or passed through the absorber without interacting. The Monte Carlo model assessed the contributions of photoelectric absorption, Compton scattering and pair production to the total mass attenuation coefficient for each type of materials under study. The simulated results of mass attenuation coefficients were compared with theoretical values obtained with XCOM database program. The theoretical calculations were in good agreement with their simulated results. The relative deviation between the results of simulation and theoretical data was less than 2%. In conclusion, an accurate Monte Carlo model was constructed and may be used to calculate the gamma rays attenuation coefficients in any given material. Furthermore, the model may be modified to estimate the radiation doses due to interactions of gamma rays with the shielding material.